Marketing mobilny - nowym sposobem komunikacji z klientem - Sobieska-Karpińska, Jadwiga; Kutera, Robert (Mobile Marketing as a New Way of Communication with Customers, 2007)
This article presents overview of development of mobile marketing in Poland. The current situation in the Polish telecommunications market was also taken under consideration. It shows the specificity of cellular telephony in the context of its use in marketing and how it changed the way businesses of every size can get their marketing messages across to customers. Mobile marketing is compared with other kinds of marketing to show its advantage as a medium of business communication between companies and consumers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 76-89